2019
DOI: 10.3747/pdi.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

The Iron Biology Status of Peritoneal Dialysis Patients May be a Risk Factor for Development of Infectious Peritonitis

Abstract: Background Infectious peritonitis is a clinically important condition contributing to the significant mortality and morbidity rates observed in peritoneal dialysis (PD) patients. Although some of the socioeconomic risk factors for PD-associated peritonitis have been identified, it is still unclear why certain patients are more susceptible than others to infection. Methods We examined the molecular components of human peritoneal dialysate (HPD) in an attempt to identify factors that might increase patient susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Although improvements in PD technology and intensive patient training in aseptic technique have reduced the incidence of skin microbe-associated peritonitis, it remains unclear as to why certain PD patients are more susceptible than others to infection. Aldriwesh et al [87] collected samples from nine patients at PD initiation and later in therapy in order to identify factors that may increase patient susceptibility to infection. They initially found that three bacteria (Staphylococcus aureus, Staphylococcus epidermidis, and Klebsiella pneumoniae), typically involved in peritoneal infections, grew in PDE with variability between patients but did not do so when incubated with the PD solution.…”
Section: Peritonitismentioning
confidence: 99%
See 3 more Smart Citations
“…Although improvements in PD technology and intensive patient training in aseptic technique have reduced the incidence of skin microbe-associated peritonitis, it remains unclear as to why certain PD patients are more susceptible than others to infection. Aldriwesh et al [87] collected samples from nine patients at PD initiation and later in therapy in order to identify factors that may increase patient susceptibility to infection. They initially found that three bacteria (Staphylococcus aureus, Staphylococcus epidermidis, and Klebsiella pneumoniae), typically involved in peritoneal infections, grew in PDE with variability between patients but did not do so when incubated with the PD solution.…”
Section: Peritonitismentioning
confidence: 99%
“…Interestingly, analysis of the iron binding status of peritoneal transferrin found it to be iron-saturated, which indicates no further iron-limitation protection against pathogens such as that created by transferrin in the blood [88]. Upon using radioactive iron-labeled transferrin, peritoneal transferrin was found as a potential direct iron source for the growth of bacteria causing peritonitis [87]. Moreover, adrenalin and noradrenalin were found in PDE and may be involved in enhancement of bacteria growth via transferrin iron provision.…”
Section: Peritonitismentioning
confidence: 99%
See 2 more Smart Citations
“…In Actinobacillus pleuropneumoniae, mutation of the gene encoding TonB2 protein prevents growth stimulation by catecholamines (Li et al, 2015), and in Aeromonas hydrophila, the increase of bacterial growth due to these molecules seems also dependent on TonB2-energy transduction system (Dong et al, 2016). Recently, Aldriwesh et al (2019) showed that Epi and NE present in peritoneal dialysate can enhance the development of bacteria and the infection risk via transferrin iron provision. All these results showed that catecholamines can increase growth of several bacteria, and that this effect may be, in part, closely related to iron homeostasis.…”
Section: Modulation Of Bacterial Physiology Effect On Growth and Capture Of Ironmentioning
confidence: 99%